Fishing boats of the world : 2 - Traung, Jan-Olof (London : Fishing News, 1960)
Proceedings and papers of the World Fishing Boat Congress (called 1953 International Fishing Boat Congress) 1st- 1953-
Includes bibliographical references and index.
Summaries in French and Spanish, v. 2-
Conference for 1953-1967 sponsored by the Food and Agriculture Organization of the United Nations.
Imprint varies: [v. 1], by the Fishing News--Arthur J. Heighway Publications Ltd.
Keywords: Fishing boats -- Periodicals -- England